2017
DOI: 10.1016/j.ajog.2017.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Prospective association of fetal liver blood flow at 30 weeks gestation with newborn adiposity

Abstract: Background The production of variation in adipose tissue accretion represents a key fetal adaptation to energy substrate availability during gestation. Because umbilical venous blood transports nutrient substrate from the maternal to the fetal compartment, and the fetal liver is the primary organ where nutrient inter-conversion occurs, it has been proposed that variations in the relative distribution of umbilical venous blood flow shunting either through ductus venosus or perfusing the fetal liver represents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…In fetal lamb, occluding the DV and forcing all UV blood to perfuse the fetal liver, leads to increased liver weight, cell proliferation, and differential fetal organ growth . Up‐regulation of the UV blood distribution to the liver is believed to be an important mechanism underlying the development of macrosomia and increased fat accretion , and the present study has demonstrated this flow pattern in PGDM pregnancies. However, in macrosomia without DM, the UV flow volume accelerates during the third trimester, supporting the increased growth velocity, whereas the DV flow volume remains unchanged .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In fetal lamb, occluding the DV and forcing all UV blood to perfuse the fetal liver, leads to increased liver weight, cell proliferation, and differential fetal organ growth . Up‐regulation of the UV blood distribution to the liver is believed to be an important mechanism underlying the development of macrosomia and increased fat accretion , and the present study has demonstrated this flow pattern in PGDM pregnancies. However, in macrosomia without DM, the UV flow volume accelerates during the third trimester, supporting the increased growth velocity, whereas the DV flow volume remains unchanged .…”
Section: Discussionsupporting
confidence: 58%
“…The distribution of the blood flow through the UV and DV develop differently in fetuses with normal growth, growth restriction, and macrosomia without maternal diabetes . This suggests that the umbilical supply to the liver plays a role in regulating fetal growth and fat deposition , with possible lifelong consequences . The DV shunts oxygenated UV blood to the fetal heart and brain, bypassing the liver , and increased shunting serves as a protective mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…3 Several human studies in low risk populations have demonstrated a positive association between fetal liver flow and fetal variables such as growth, birth weight, 29,30 and fat deposition. 3,4 Growth restricted fetuses often display increased head-abdomen (HC/AC) ratio as well as increased DV-shunting fraction. This is assumed to ensure oxygen and nutritional supply to vital organs as the brain and heart.…”
Section: Discussionmentioning
confidence: 99%
“…6 Interestingly, Ikenoue et al found a significant correlation between fetal liver flow and newborn fat percentage, but in subclass analyses the relation was strengthened in the maternal normal-weight group and disappeared in the overweight group. 4 Body mass index (BMI) is often used as a proxy for body fat mass. In early pregnancy, BMI measures correlate better with body fat mass than BMI measures later in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation